Place, Space and Community: Enhancing community identity in Winona, Kansas - Barrett, Kirby (Kansas State University, 2011)
The sub-rural Kansas community of Winona stands at a critical crossroad. The dilemma of rural population decline, fueled largely by technological advances in communication, transportation, and agriculture is devastating rural economies and the centers of community social life – namely the local school(s) and main street(s). The physical infrastructure, spatial character and unique identity of rural places is slowly diminished in the process. While great potential exists for the landscape architecture and planning professions to address the patterns of rural decline, the limited market for such services and the lack of regulations requiring those services precludes their effective implementation within rural communities. Within Winona, a long-standing stormwater problem provides an opportunity to address both the stormwater problem and the larger dilemma in a holistic landscape architecture approach. How can contemporary landscape architecture engage rural communities in planning and design solutions aimed at mitigating stormwater issues while addressing community identity loss resulting from population and economic decline? The Place, Space, Community (PSC) Framework developed can determine distinctive qualities and characteristics and illuminate community identity which serves as the creative genesis for stormwater mitigation, and more importantly, the development of social capital critical to economic and population stability and growth. Successful development of social capital and enhanced community identity is dependent on design solutions anchored in the sense of place inherent in the residents of Winona. Landscape architects are uniquely qualified to provide solutions to the stormwater problem which respond to place in ways influencing the identity and social capital of Winona’s residents in dramatically positive ways. This initial focus on a holistic, place-based approach to increased social capital provides a strong foundation for future economic, social and environmental stability and growth into the future. Winona can indeed enjoy a bright and prosperous future with a Place, Space, Community approach.
Keywords: Landscape Architecture/Planning; Community Capitals; Stormwater BMPs; Rural Kansas; PSC Framework; Place and Identity; Winona, Kansas; Design (0389); Landscape Architecture (0390)